Creative spaces seeking the dynamics of change in China - Gimpel, Denise; Nielsen, Bent; Bailey, Paul John (NIAS studies in Asian topics, 2012)
Explores new ways to understand the dynamics of change and mobility in ideas, people, organizations, and cultural paradigms, and uses case studies of change in China past and present but offers global (and not just Chinese) insights